How Does Initial Teacher Education Research Frame the Challenge of Preparing Future Teachers for Student Diversity in Schools? A Systematic Review of Literature. (February 2021) - Rowan, Leonie; Bourke, Terri; L'Estrange, Lyra; Lunn Brownlee, Jo; Ryan, Mary; Walker, Susan; Churchward, Peter
Teachers consistently identify working with "diverse learners" as challenging. This raises questions about how teacher educators conceptualize and enact preparation of teachers for heterogeneous populations. This article provides a systematic review of literature relating to both "teacher education" and "diverse learners, " to identify knowledge claims regarding the way this "problem" and possible "solutions" should be framed. Analyzing 209 peer-reviewed journal articles (2009–2019), the article identifies groups most frequently described as diverse, three qualitatively different clusters of claims regarding how teachers can be prepared for diversity, and factors identified as constraining preparation. Analysis reveals a literature broad in focus—referencing many groups—but shallow in depth. The majority describe strategies for teaching about or catering to diversity with only few considering teaching for diversity. There is also limited engagement with specialist literature relating to concepts such as gender or race and little attention to teacher educators' own knowledge. The article concludes with implications for teacher educators, arguing for enhanced critical epistemic reflexivity.